Role of traditional institutions in conservation of plant diversity (2010)
Plant diversity is the vast variety of plant life and its ecological complexities existing in any region. Circumstances gave rise to diverse experiences among indigenous societies about plant wealth around them. Plants are integral for the survival of the traditional culture. Each community has a unique set of social institutions. Conservation efforts can be more efficient if it is based on deep knowledge of social institutions. Plant diversity conservation thrive if synchronizes with improvement in human welfare. It is imperative that plant diversity conservation and its sustainability should focus traditional institutions because of its voluntary compliance features and cost effectiveness. This review focuses on critical factors in traditional institution that can affect conservation of plant diversity. These factors include local attitude, land use change, indigenous knowledge, religious belief, and cultural traditions.